Proving the automatic benchtop electrochemical station for the development of dopamine and paracetamol sensors - Haššo, Marek; Kudr, Jiří; Zítka, Jan; Šílený, Jan; Švec, Pavel; Švorc, Ľubomír; Zítka, Ondřej (Mikrochimica acta, 2024)
The introduced work represents an implementation of the automatic benchtop electrochemical station (BES) as an effective tool for the possibilities of high-throughput preparation of modified sensor/biosensors, speeding up the development of the analytical method, and automation of the analytical procedure for the determination of paracetamol (PAR) and dopamine (DOP) as target analytes. Within the preparation of gold nanoparticles modified screen-printed carbon electrode (AuNPs-SPCE) by electrodeposition, the deposition potential EDEP, the deposition time tDEP, and the concentration of HAuCl4 were optimized and their influence was monitored on 1 mM [Ru(NH3)6]3+/2+ redox probe and 50 μM DOP. The morphology of the AuNPs-SPCE prepared at various modification conditions was observed by SEM. The analytical performance of the AuNPs-SPCE prepared at different modification conditions was evaluated by a construction of the calibration curves of DOP and PAR. SPCE and AuNPs-SPCE at modification condition providing the best sensitivity to PAR and DOP, were successfully used to determine PAR and DOP in tap water by "spike-recovery" approach. The BES yields better reproducibility of the preparation of AuNPs-SPCE (RSD = 3.0%) in comparison with the case when AuNPs-SPCE was prepared manually by highly skilled laboratory operator (RSD = 7.0%).
Keywords: Electrochemical Techniques; kovové nanočástice; Electroplating; Sensor array; Screen-printed electrode; zlato; Differential pulse voltammetry; Dopamine; Electrodeposition; Metal Nanoparticles; Biosensing Techniques; limita detekce; Electrodes; paracetamol; elektrochemické techniky; biosenzitivní techniky; dopamin; Acetaminophen; Limit of Detection; elektrody; Gold; Carbon; uhlík